Urban Risk Assessment of Lahar Flows in Merapi Volcano (Study Case: Muntilan Urban Area, Central Java) - Cosmas Bambang Sukatja; Sudibyakto Sudibyakto; RPGA Voskuil (Indonesian Journal of Geography, 2014)
The objective of the research was to analyse probability of lahar flows occurrence in Muntilan urban area,Central Java. By using integrated methods, which involve the numerical simulation program, Geographic InformationSystem (GIS), Remote Sensing (RS) and field verification to produce lahar flows Hazard Map and Risk Map. Muntilanurban area located at western flank of Merapi volcano, and in down stream of Lamat river. The river is Lahar River thatis endangering from Merapi volcano, which flowing down to cuts a cross of that area. Therefore, Muntilan urban areais vulnerable area from lahar flows disaster. Lahar flows, generally occur during intense rainfall on saturated volcanicdeposit in upper stream of river or wall of volcano. Lahar flows are extremely dangerous especially to those living invalley areas near a volcano, which can undercut banks and cause houses destruction situated on the banks, and canbury and destroy resident, structures, infrastructure facilities including roads and bridges. Meanwhile, development ofMuntilan urban area that caused many illegal settlements appears surrounding that area. Occasionally, un-benefit peopleconstructing house in disaster prone area, such as down stream of river side that have lahar flows risk. The research wasconcluded that lahar flow occurrence in 100 years return period will be buried the Muntilan urban area. With the methodsintegrating of GIS, RS, field verification can be done analysing of lahar flows hazard map, and risks map to producerisk assessment in Muntilan urban area.